Global systematic diversity, range distributions, conservation and taxonomic assessments of graylings (Teleostei: Salmonidae; Thymallus spp.) - Steven J. Weiss; Duarte V. Gonçalves; Giulia Secci-Petretto; Gernot K. Englmaier; André Gomes-Dos-Santos; Gael P. J. Denys; Henri Persat; Alexander Antonov; Christoph Hahn; Eric B. Taylor; Elsa Froufe (Organisms Diversity & Evolution, 2021)
Graylings ( Thymallus ) are among the less well-studied groups of salmonid fishes, especially across their Asian distribution range. Here we perform a comprehensive global review of their phylogeography, systematic diversity and range distributions, including biogeographic reconstruction and assessment of both conservation and taxonomic status of each species. Based on a mitogenomic phylogenetic analysis, three approaches to the delineation of molecular operational units, and evaluation of 15 a-priori defined species, we provide biological support for the recognition of 13 grayling species, plus two additional species tentatively. Several instances of paraphyly and its potential effect on systematic inferences are discussed. Overall, the genus displays increasing species diversity and decreasing range size from higher to lower latitudes and ancestral trait reconstruction supports an East Asian origin for extant diversity, most likely centred in the Amur River drainage. Europe’s colonization by Thymallus took place as early as the late Miocene, at least two colonisations of North America are supported, and multiple dispersal events likely took place into Western Siberia. The conservation status for the 15 taxa was estimated to be: 6 least concern, 1 near-threatened, 2 vulnerable, 3 endangered and 3 data deficient.